Canopy specialist Hylaeus bees highlight sampling biases and resolve Michener’s mystery - Dorey, James B.; Davies, Olivia K.; Magnacca, Karl N.; Schwarz, Michael P.; Gilpin, Amy-Marie; Ramage, Thibault; Tuiwawa, Marika; Groom, Scott V. C.; Stevens, Mark I.; Parslow, Ben A. (Frontiers in Ecology and Evolution, 2024)
Large parts of the Pacific were thought to host low bee diversity. In Fiji alone our recent estimates of native bee diversity has rapidly increased by a factor of five (from four to >22). Here we show how including sampling of the forest canopy has quickly uncovered a new radiation of Hylaeus (Hymenoptera: Colletidae) bees in Fiji. We also show that Hylaeus are more common across the Pacific than previously thought and solve one of Charles Michener’s mysteries by linking the previously enigmatic French Polynesian Hylaeus tuamotuensis to relatives in Fiji. We use systematic techniques to describe eight new Hylaeus species in Fiji (n = 6), French Polynesia (1), and Micronesia (1), and discuss impressive dispersal events by this genus. These clades also double the number of Hylaeus dispersals out of Australia from two to four. Our discovery highlights the severe impact of bee sampling methods on ecological interpretations and species discovery, specifically that canopy sampling is needed to correctly assess forest bee diversity even where there is a very long record of sampling. It further highlights the potential for forests to host higher than anticipated diversity and conservation value. This has broad methodological and regulatory impacts for land managers seeking to make choices about pollination services and diversity. The new species are Hylaeus (Euprosopoides) chuukensis Dorey, Davies, and Parslow; H. (Prosopisteron) albaeus Dorey, Davies, and Parslow; H. (P.) apertus Dorey, Davies, and Parslow; H. (P.) aureaviridis Dorey, Magnacca, and Parslow; H. (P.) breviflavus Magnacca; H. (P.) derectus Dorey, Davies, and Parslow; H. (P.) navai Dorey, Davies, and Parslow; and H. (P.) veli Dorey, Davies, and Parslow.